18. RESULTS OF TREATMENT OF THREATENED MISCARRIAGE UNDER 12 WEEKS AND SOME RELATED FACTORS AT THAI BINH OBSTETRICS HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the treatment outcomes of threatened miscarriage under 12 weeks and its related factors at Thai Binh Obstetrics and Gynecology Hospital in 2024.Method: A prospective cross-sectional descriptive study was conducted on 151 pregnant women diagnosed with threatened miscarriage at ≤ 12 weeks of gestation at Thai Binh Obstetrics and Gynecology Hospital from January 1, 2024, to June 30, 2024.Results: The overall treatment success rate was 90.7%. Univariate regression analysis showed two statistically significant factors associated with treatment failure: maternal age ≥ 35 years (OR = 10.53; 95%CI: 3.19-34.67; p < 0.05) and a history of miscarriage or stillbirth (OR = 13.12; 95%CI: 2.81-61.17; p < 0.05).Conclusion: The treatment of threatened miscarriage ≤ 12 weeks at Thai Binh Obstetrics and Gynecology Hospital achieved a high success rate. Maternal age ≥ 35 years and a history of miscarriage or stillbirth are independent prognostic factors related to treatment failure. Closer monitoring and counseling for this high-risk group of pregnant women are necessary.
Keywords: Threatened miscarriage; treatment outcome; related factors.